Standardized testing - Bryfonski, Dedria (Farmington Hills, Michigan Greenhaven Press, 2012)
"Standardized Testing: Books in this anthology series focus a wide range of viewpoints onto a single controversial issue, providing in-depth discussions by leading advocates, a quick grounding in the issues, and a challenge to critical thinking skills"--Provided by publisher.
Standardized tests effectively measure student achievement / Herbert J. Walberg -- Standardized tests do not effectively measure student achievement / Phillip Harris, Bruce M. Smith, and Joan Harris -- Standardized testing encourages teachers to be creative / Stuart Buck ... [et al.] -- Standards and assessments are not always meaningful / Rob Montgomery -- Value-added modeling is the best tool to measure teacher effectiveness / Staven Glazerman et al. -- Value-added modeling does not fully measure teacher effectiveness / Eva L. Baker et al. -- The pressure to meet targets has caused teachers to cheat / Teacher World -- Cheating on test scores does not invalidate the need for testing / Saba Bireda -- No Child Left Behind testing has produced benefits / Greg Foster -- SAT scores help colleges make better decisions / Gaston Caperton -- Colleges do not need SAT scores to be selective in admissions / Ann B. McDermott -- The SAT test may discriminate against African Americans / Jay Mathews -- A lack of reading causes African Americans to fare poorly on the SAT test / Veda Jairrels.
Includes bibliographical references and index.
Keywords: Educational tests and measurements -- United States -- Juvenile literature; Educational tests and measurements -- United States -- Juvenile literature